Non‐biofilm‐forming commensal Staphylococcus epidermidis isolates produce biofilm in the presence of trypsin - Martínez‐García, Sergio (Microbiologyopen, 2019)
Epidemiological studies comparing clinical and commensal Staphylococcus epidermidis isolates suggest that biofilm formation is a discriminant biomarker. A study showed that four non‐biofilm‐forming clinical S. epidermidis isolates could form an induced biofilm by trypsin treatment, suggesting that S. epidermidis can form biofilms in a protease‐independent way and in a trypsin‐induced way. In this study, the trypsin capacity to induce biofilm formation was evaluated in non‐biofilm‐forming S. epidermidis isolates (n = 133) in order to support this mechanism and to establish the importance of total biofilms (meaning the sum of protease‐independent biofilm and trypsin‐induced biofilm). Staphylococcus epidermidis isolates from ocular infections (OI; n = 24), prosthetic joint infections (PJI; n = 64), and healthy skin (HS‐1; n = 100) were screened for protease‐independent biofilm formation according to Christensen's method. The result was that there are significant differences (p < .0001) between clinical (43.2%) and commensal (17%) protease‐independent biofilm producers. Meanwhile, non‐biofilm‐forming isolates were treated with trypsin, and biofilm formation was evaluated by the same method. The number of commensal trypsin‐induced biofilm producers significantly increased from 17% to 79%. In contrast, clinical isolates increased from 43.2% to 72.7%. The comparison between clinical and commensal total biofilm yielded no significant differences (p = .392). A similar result was found when different isolation sources were compared (OI vs. HS‐1 and PJI vs. HS‐1). The genotype icaA (−) /aap (+) was associated with the trypsin‐induced biofilm phenotype; however, no correlation was observed between aap mRNA expression and the level of trypsin‐induced biofilm phenotype. Studying another group of commensal S. epidermidis non‐biofilm‐forming isolates (HS‐2; n = 139) from different body sites, it was found that 70 isolates (60.3%) formed trypsin‐induced biofilms. In conclusion, trypsin is capable of inducing biofilm production in non‐biofilm‐forming commensal S. epidermidis isolates with the icaA (−) /aap(+) genotype, and there is no significant difference in total biofilms when comparing clinical and commensal isolates, suggesting that total biofilms are not a discriminant biomarker.